Design, Implementation, and Evaluation of a Telehaptics System over a 4G Mobile Network Testbed - Chepkoech, Maurine (Department of Electrical Engineering, 2024)
Telesurgery, the remote provision of surgical services using robotics and information communication technologies, will contribute to addressing the shortage of surgeons and the limited access to advanced surgical services, especially in low- and middle-income countries (LMICs). However, the realization of these systems is hampered by a lack of supporting technologies, unreliable communication networks, and costly surgical equipment. For instance, most of the existing telesurgery systems only rely on audio and visual feedback during an operation. However, achieving high-fidelity remote operation requires adequate involvement of human senses beyond audio and visual data. This can be done by integrating haptic feedback. Haptic feedback entails the transmission and perception of the human sense of touch. In telesurgery, haptics will improve the accuracy of the procedure by enabling the surgeon to feel the consistency of force against body tissues and differentiate between bones, flesh, and body fluids. Therefore, this work presents the design and development of a telehaptics system for transmitting haptic feedback over a distance for possible integration into teleoperation systems, such as telesurgery. Haptic communication requires stringent network performance, including low end-to-end latency of less than 10 ms and ultra-reliability, i.e., greater than 99.99%, for an interactive experience. These requirements can be achieved over modern mobile networks such as 4G and 5G. Unfortunately, mobile network coverage in most LMICs is limited, with the dominant technologies being 2G and 3G. Consequently, 4G and 5G mobile network testbeds have been implemented using open-source software frameworks and commercial radio equipment to achieve haptic communication's stringent latency and reliability requirements. The developed testbed provides a platform to evaluate and validate the telehaptics system before its integration into real-world telesurgery systems. The open- source approach adopted in realizing the 4G and 5G mobile network testbed overcomes the rigid and expensive proprietary restrictions and achieves permissionless, faster, cheaper, and more flexible modern network deployment. All haptic data packets were delivered to the slave node in the forward transmission loop, and to the master node in the feedback loop and an average end-to-end latency of 10 ms was achieved from the evaluation of the prototype telehaptics system over the configured 4G mobile network testbed. On the other hand, while the 5G mobile network testbed was configured and deployed, its connection was unstable, and average end-to-end latency performance was above the requirements for haptic communication, i.e. 12 ms. This was due to the bandwidth limitation in the current release of the open-source 5G radio access network software stack, srsRAN, used in testbed implementation. Consequently, due to the unstable connection, the 5G mobile network testbed could not support the experimentation period for the prototype telehaptics system. Hence, future developments of this work will entail fine-tuning the 5G network testbed to achieve less than 5 ms end-to-end latency and greater than 99.999% reliability, as specified in the 3rd Generation Partnership Project standards.